Sorghum Sticks (Sorghum bicolor) with Added Protein Source: Dumbo Catfish Meal (Clarias gariepinus) - Rahardiantoro, Ryan; Noerhartati, Endang; Rahayuningsih, Tri (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: The study aims to determine the combination of selected treatments in the proportion of sorghum flour: wheat and the amount of dumbo catfish meal and the financial feasibility of the sorghum stick business. Design/methodology/approach: The study used a Group Randomized Design (RAK) factorial pattern with factor (P) proportion of sorghum flour: wheat (P1 = 25:75, P2 = 50:50, and P3 = 75:25) and factor (K) concentration of dumbo catfish meal (K1 = 20% and K2 = 30%), with three repeats. Observations in the study include analysis of protein, fat, water, ash, total and carbohydrate levels, yield tests, developmental tests, and organoleptic tests, including preferences for colour, aroma, taste, crispness, and texture. Data processing of protein, fat, water, ash, carbohydrate, yield, and growth values is analyzed using fingerprints (ANOVA). If there is a fundamental difference, it will be continued with the Duncan test with a confidence level of 95%. Organoleptic test data uses the Friedman test. Alternative selection is done to determine the selected treatment using the Expected Value method. The Weight test method is carried out to determine the importance of the weight of each parameter. The financial feasibility of the sorghum stick business in this study uses the BEP (Break Even Point), NPV (Net Present Value), IRR (Internal Rate of Return), and PP (Payback Period) methods. Findings: Based on the study's results, the P1K2 treatment (proportion of sorghum flour: wheat flour 40:60 and dumbo catfish flour concentration 30%) became the selected treatment with an expectation value of 8.20. This treatment yields 74.92%, water content 12.59%, ash content 3.65%, protein content 8.99%, fat content 19.49%, carbohydrate content 55.28%, and development power 95.58%. It has a total percentage of liking for colour 96.7%, aroma 94.5%, taste 88.9%, and texture 98.9%. The results of the financial analysis of sorghum sticks are worthy of development, with BEP parameters of 20,623 packs equivalent to IDR 408,294,154.00, NPV of IDR 116,980,531.71, IRR reaching 17.79%, PP 3 years 3 months. Research limitations/implications: This research is specifically for the development of a sorghum stick product entrepreneurial with Added Protein Source: Dumbo Catfish Meal (Clarias gariepinus) Practical implications: The development of sorghum-based entrepreneurship products must continue to be promoted to continue to support food security